126k views
2 votes
5 (6 - x) - 3 = 5 + 4 (x + 3)​

User Matekus
by
4.1k points

2 Answers

3 votes

Answer:

X=0

Explanation:

5(6-X)-3=5+4(X+3)

30-5x=5+4x+12

30-5-12=4x+5x

13=9x

13/9=x

User Tommy Saechao
by
4.7k points
6 votes

Answer:

Use BODMAS rule

1st:B- solve bracket

2nd-O- open bracket

3rd;D:divide

4th:M- multiply

5th:A- Addition

6th :Subtract

Solution given;

5 (6 - x) - 3 = 5 + 4 (x + 3)

open bracket

30-5x-3=5+4x+12

30-3-5-12=5x+4x

10=9x

x=10/9

x=10/9

User AmiguelS
by
5.3k points